Biological Treatment Of Spent Coffee Ground (Scg) And Its Influence On The Mechanical Properties Of Biopolymer Composite - Boey, Jet Yin (2023)
This study aimed to develop biomass-reinforced biocomposites by employing spent coffee grounds (SCG) as reinforcement material and poly(lactic acid) (PLA), and poly(hydroxyalkanoate) (PHA) as the matrix. The investigation focused on assessing the effect of SCG content (10–40 wt%) and the PHA/PLA ratio (100/0, 75/25, 50/50, 25/75, and 0/100) on the properties of these biocomposites. The compounding process was conducted using a twin-screw extruder at a temperature of 220˚C at the feeding zone and 210˚C at the mixing zone at a rotating speed of 75 rpm. The mixture was then cooled and pelletized before it was compressed at a temperature of 190˚C using compression moulding for biocomposites making. The biocomposites were then cut according to the different testing dimensions. Incorporating SCG lowered the mechanical properties, primarily due to its incompatibility with the PHA/PLA matrix. This observation was confirmed through morphological analysis, which revealed a gap between the SCG and the matrix. SCG displayed a tendency to aggregate at loading of 40 wt%, leading to increased void formation (8.2–9.1%) compared to lower loading at 10 wt% (7.6–8.1%). A PHA/PLA ratio (50/50) with SCG loading (20 wt%) was chosen to make biocomposites with treated SCG. Biological treatment of SCG using P. chrysosporium CK01 and A. niger DWA8 indicated P. chrysosporium CK01 necessitated a higher moisture content (55%, w/w) for optimum growth and enzyme production, while the optimal condition for enzyme production differed from those promoting A. niger DWA8 growth.